A Comprehensive Narrative Review of the Challenges Surrounding Cutaneous SCC - Sarah C. Beach; Austin S. Cusick; Aaron S. Farberg; Shannon C. Trotter (Dermatology and Therapy)
Abstract Cutaneous squamous cell carcinoma (cSCC) is the second most common nonmelanoma skin cancer (NMSC) and is predominantly found in the head and neck region. With an annual increase in NMSC diagnoses, cSCC presents significant diagnostic and therapeutic challenges. This review discusses the many risk factors for the development of cSCC, outlines the criteria for defining high-risk cSCC, and examines treatment approaches of these tumors based on risk stratification. While most cSCCs are treatable with surgical excision, approximately 5% metastasize, with head and neck cSCC showing poor prognosis once metastasis occurs. High-risk cSCCs, which are more likely to recur or metastasize, are often characterized by larger size, deeper invasion, and histopathological features such as perineural or vascular involvement. However, there is not a standardized definition of high-risk cSCC, leading to variability in prognosis and treatment approaches. While widely adopted staging systems such as the American Joint Committee on Cancer 8th Edition (AJCC8) and the Brigham and Women’s Hospital (BWH) classification provide a useful framework based primarily on tumor size and extent, they have limitations—particularly in accounting for patient-specific factors. Given the complexity of factors involved in clinical decision-making, treatment recommendations warrant a case-by-case application of criteria on an individualized level, incorporating variables beyond conventional staging paradigms. While surgical excision is indicated for high-risk invasive cSCC, other treatments may include adjuvant radiation therapy (ART) and systemic therapies such as immune checkpoint inhibitors (cemiplimab, pembrolizumab, and cosibelimab) and epidermal growth factor receptor (EGFR) inhibitors (cetuximab). Gene expression profiling (GEP) is a tool that offers prognostic information to help assess metastatic risk and guide treatment decisions; however, prospective, nonbiased studies are needed to validate its utility to support broader integration into clinical practice. Despite advancements, inconsistent application of ART and biopsy limitations persist, highlighting the need for a standardized, evidence-based approach to cSCC management. This review highlights the challenges surrounding cSCC and the potential value of molecular tools to improve outcomes for patients with high-risk cSCC.